A Molecular Dynamics Study of Subsurface Hydrogen-Helium Bubbles in Tungsten. (2nd January 2017) - Bergstrom, Z. J.; Cusentino, M. A.; Wirth, B. D.
Abstract : Fusion reactor materials experience high ion fluxes and operating temperatures, which will ultimately produce subsurface helium and hydrogen bubbles in the tungsten divertor that can cause surface degradation and impact core plasma performance. Molecular dynamics simulations have been used to evaluate the behavior of hydrogen and helium near a 2-nm bubble or void below a tungsten surface as a function of surface orientation, temperature, gas atom concentration, initial hydrogen distribution, and depth below the surface. A clear tendency for hydrogen to segregate to the bubble-matrix interface is observed in these simulations, regardless of the initial spatial distribution of the hydrogen or simulation parameters. This segregation is due in part to a local minimum in the hydrogen energy at the periphery of the bubble. Further work is required to fully characterize the mechanism of this behavior and to assess the quantities of hydrogen in the bubble and at the bubble periphery.